Assessment of meteorological drought in agricultural locations from Venezuela under future projections of climate change - Silva Borges, Miguel I.; Mendoza D., Naghely M. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Drought is a phenomenon that is difficult to detect and predict, and with devastating consequences for natural, agricultural and human ecosystems. In order to know the future effects that climate change could have on this phenomenon in eight agricultural localities of Venezuela, the changes in the magnitude and duration of meteorological drought events were evaluated, for the reference series and for future series (period 2050s), projected by NCAR-CCSM4, GISS-E2-R, NIMR-HADGEM2-AO and MPI-ESM-LR models, for RCP 2.6 and RCP 8.5 scenarios. Drought events were estimated using the Standardized Precipitation Index (SPI) for the monthly scale and keeping the shape and scale parameters of the reference period. The results reveal a high variability of drought events among stations, models and scenarios; but with a common increase of the magnitude and duration of drought events for all models, mainly under the RCP 8.5 scenario. For the NCAR-CCSM4 model, there would be the greatest increase in the analyzed characteristics, in contrast to the NIMR-HADGEM2-AO model. The localities with droughts of greater magnitude and duration would be Barinitas and Pariaguán.Key words: drought, climate change, models, period, climate.